Ecocide in international law: draft definition for the Rome Statute - Tulibayev, S.T. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
This article examines the novel approach to defining ecocide. The legal theory concerning ecocide is still in the development stage without an internationally recognized definition of ecocide. However, a recent proposal to recognize ecocide as one of the international crimes and a component of the Rome Statute may be a significant step in the development of ecocide theory. The investigation’s purpose is to analyze a new approach to ecocide and issues of the establishment of practical definition for subsequent amendments in Kazakhstan legislation. The author compares the definition of ecocide in the Criminal Code of the Republic of Kazakhstan to the new draft definition of ecocide in the Rome Statute using both general and specialized research methodologies. The article concludes that international recognition of ecocide creates an opportunity to develop an effective legal system that can preserve and protect our planet. Furthermore, the author argues that such practical international legal instrument as the Rome Statute needs recognition and ratification in Kazakhstan.